The Construction of Stunting Issues in Social Media: Analysis of Public Issues in Digital Health Campaigns in Indonesia - Hasrimy, Muhammad Faisal; Mailin, Mailin (Program Pascasarjana UIN Sumatera Utara, 2025)
In the digital era, social media has evolved into a dominant public space that shapes discourse, mobilizes participation, and influences public perception—especially in health communication. This study examines how the issue of stunting is socially constructed in Indonesia’s digital space and how public health campaigns on social media influence public perception and engagement. Using a qualitative descriptive approach and Fairclough’s Critical Discourse Analysis (CDA), complemented by Entman’s framing theory and light quantitative trend analysis, this research analyzes the narratives, symbols, and interactions surrounding stunting-related digital campaigns such as #CegahStunting and #BapakAsuhAnakStunting The findings reveal that stunting is framed as a collective moral issue tied to the nation's future, with families—especially parents—portrayed as central actors in its prevention. Social media content constructs this issue through persuasive language, hashtags, visual storytelling, and the strategic use of influential public figures and institutions. Framing elements such as problem identification, causal attribution, moral evaluation, and treatment recommendations are found to be consistently applied in constructing public meaning and shaping behavior. Public engagement manifests through digital activism, content sharing, and the emergence of grassroots health communities. However, the study also identifies counter-narratives criticizing the moralistic framing that disproportionately blames families while overlooking structural inequalities This research contributes to the discourse on health communication and public engagement by highlighting the dual function of social media as both a platform for education and a contested space for narrative negotiation. It offers practical implications for more inclusive, participatory, and context-sensitive digital health campaigns in Indonesia’s multisectoral stunting reduction strategy.